Parish churches in the early modern world
1 online resource (xv, 404 pages)
Keywords: "Across Europe, the parish church has stood for centuries at the centre of local communities; it was the focal point of its religious life, the rituals performed there marked the stages of life from the cradle to the grave. In spite of the importance of the parish church, these buildings have generally not received the same attention from historians as non-parochial places of worship. This collection of essays redresses this balance and reflects on the parish church across a number of confessions during the early modern period. This interdisciplinary volume seeks to identify what was distinctive about the parish church for the congregations that gathered in them for worship and for communities across the early modern world"--